CIPO Model Oriented Designing Online Teaching for the Technology Subject at High Schools - Nguyễn Thị Duyên; Bùi Văn Hồng; Võ Phi Nghịch; Phạm Thị Quỳnh Anh (Journal of Technical Education Science, 2024)
The CIPO model (Context - Input - Process - Output) is commonly applied in the design and management of teaching activities, including online teaching. This model easy to apply based on the elements of model as context (C), input (I), process (P) and output (O), that are described specifically and systematically, making it easy to apply, not only helping to organize and manage the teaching activities, it can also be easily applied to many different aspects of education, including: designing and managing educational programs, evaluating learning effectiveness, developing teaching technology, etc. Based on the systematic nature and flexibility of the model, CIPO provides a foundational framework for improving, innovating and managing education, especially in the context of increasingly developing technology. This study is based on the CIPO model to design online teaching for the Technology subject in high schools. Through determining the impact of the technological development context on teaching, the necessary input factors for online teaching, the process of operating online classes, students' learning outcomes, authors design of online teaching on the illustration topic of Plant Growing Media in the Technology grade 10, and evaluating the feasibility and effectiveness of the research results by survey and experiment methods at Ben Cat High School, Binh Duong province. Research results show that students have positive changes in their creativity, problem solving, teamwork and use of digital technology. Designing online teaching of Technology subject based on the CIPO model has brought many benefits to the teaching process, but it requires careful preparation of techniques and digital pedagogical capacity for teachers.